“Diseño de un sistema de costos por proceso para la Agrícola Bananera San José del Recinto San Eduardo del Cantón La Maná” - Chiliquinga Ninasunta, Carmen del Rocío (2020)
The present research work was focused on structuring a process cost system for the banana farm San José in San Eduardo village, La Maná canton, Cotopaxi province. The methodology used was through bibliographic research to collect theoretical data, field research at the time of applying interviews to the owner and accountant, descriptive research for the description of each of the costs in each productive phase. The methods used were: the inductive, deductive and the interview technique. The production process begins with the preparation of the land, the maintenance phase consisting of deforestation, and scrapping, propping up, fertilization, pest control, sheathing, surgery and the harvesting process involved aspects such as the previous cluster calibration to the cut, after which it crumbles, transport in the funicular line, sanitation, washing, spraying, labeling, packing, vacuuming, is in the truck that moves to the port in Guayaquil city. The cost determination yielded a value of $ 61, 39 for direct inputs, direct labor was $ 434, 13 and indirect costs reflected a value of $ 727,72. While the income generated by the sale of 331 boxes, reflected a value of $ 2.085, 30; and a net profit of $ 767,95, corresponding to the month of December, for one hectare of banana in the banana farm San José.